2016
DOI: 10.1080/0886022x.2016.1214892
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates ischemia reperfusion-induced acute kidney injury through NMDA receptor antagonism in rats

Abstract: It is concluded that NMDA receptor antagonism significantly contributes towards curcumin-mediated protection against I/R-induced AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 21 publications
5
16
0
Order By: Relevance
“…The rats were randomly equally divided into three groups ( n = 10 for each group): I/R-Curcumin group (Cur) in which the rats were subjected to renal ischemia for 45 min and precondition with 60 mg/kg (i.p. injection) of Curcumin (Sigma, St. Louis, MO) at 45 min before I/R induction; The dosage of Curcumin was in line with previous study [ 7 ]. I/R-vehicle group (IRI), in which the rats were subjected to renal ischemia for 45 min and precondition with 60 mg/kg (i.p.…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…The rats were randomly equally divided into three groups ( n = 10 for each group): I/R-Curcumin group (Cur) in which the rats were subjected to renal ischemia for 45 min and precondition with 60 mg/kg (i.p. injection) of Curcumin (Sigma, St. Louis, MO) at 45 min before I/R induction; The dosage of Curcumin was in line with previous study [ 7 ]. I/R-vehicle group (IRI), in which the rats were subjected to renal ischemia for 45 min and precondition with 60 mg/kg (i.p.…”
Section: Methodssupporting
confidence: 55%
“…I/R-Curcumin group (Cur) in which the rats were subjected to renal ischemia for 45 min and precondition with 60 mg/kg (i.p. injection) of Curcumin (Sigma, St. Louis, MO) at 45 min before I/R induction; The dosage of Curcumin was in line with previous study [ 7 ].…”
Section: Methodssupporting
confidence: 55%
“…In fact, many recent studies have also shown that curcumin may relieve damage due to AKI. Kaur et al () demonstrated that NMDA receptor antagonism significantly contributes to curcumin‐mediated protection against I/R‐induced AKI. He et al () clearly demonstrated that curcumin protects the kidney from gentamicin‐induced AKI via the amelioration of oxidative stress and apoptosis of renal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, A. Kaur et al (2016) speculated that curcumin is an NMDA receptor antagonist. Curcumin could also reverse the glutamate-induced excitotoxicity in the (a) cerebral cortex region of streptozotocin-induced diabetic rats (Jayanarayanan, Smijin, Peeyush, Anju, & Paulose, 2013), (b) PC12 cells (Chang, Chen, Yu, Peng, & Peng, 2014), and (c) SH-SY 5Y neuronal differentiated cell culture (Chen, An, Tie, Pan, & Li, 2015).…”
Section: Gabaergic and Glutamatergic Modulation By Curcuminmentioning
confidence: 99%